Optimization of a Sonotrode Extraction Method and New Insight of Phenolic Composition of Fucus vesiculosus - Lidia Gil-Martínez; Alejandro Santos-Mejías; José Manuel De la Torre-Ramírez; Alberto Baños; Vito Verardo; Ana M. Gómez-Caravaca (Marine Drugs)
The optimization of bioactive compound extraction from Fucus vesiculosus using ultrasound-assisted extraction (UAE) via sonotrode was investigated to maximize phenolic recovery and antioxidant activity while promoting a sustainable process. Optimal conditions (40% v/v ethanol in water, 38 min, 36% amplitude) were selected to maximize phenolic recovery while considering environmental and energy sustainability by optimizing extraction efficiency and minimizing solvent and energy usage. HPLC-ESI-QTOF-MS analysis tentatively identified 25 phenolic compounds, including sulfated phenolic acids, phlorotannins, flavonoids, and halophenols, with some reported for the first time in F. vesiculosus, underscoring the complexity of this alga’s metabolome. The antioxidant activity of the optimized extract was evaluated through FRAP (143.7 µmol TE/g), DPPH (EC50 105.6 µg/mL), and TEAC (189.1 µmol Trolox/g) assays. The optimized process highlights F. vesiculosus as a valuable source of natural antioxidants, with potential applications in biotechnology, cosmetics, and food industries.